Penegakan Hukum terhadap Tindak Pidana Korupsi: Studi Perbandingan Sistem Pidana Amerika Serikat, Malaysia, dan Singapura - Satriya Aldi Putrazta (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze and compare the legal systems and enforcement models for combating corruption in three countries namely the United States, Malaysia, and Singapore while identifying key lessons that can be applied to strengthen Indonesia’s anti-corruption legal framework. Although all three countries demonstrate strong commitments to eradicating corruption, each employ distinct normative and institutional approaches. The United States relies on the Foreign Corrupt Practices Act (FCPA), which emphasizes corporate liability, global jurisdiction, and is enforced by the Department of Justice (DOJ) and the Securities and Exchange Commission (SEC), supported by a robust whistleblower protection system. Malaysia, through the Malaysian Anti-Corruption Commission Act 2009, adopts a criminal law approach with a broad definition of gratification and reverse burden of proof under Section 50. Singapore, through its Prevention of Corruption Act (PCA) and the Corrupt Practices Investigation Bureau (CPIB), demonstrates highly effective enforcement despite having relatively concise regulations, owing to institutional integrity, political commitment, and administrative consistency. This research employs a normative juridical method, incorporating statutory, conceptual, and comparative approaches. Legal sources include primary legal materials (statutes and regulations), secondary legal materials (literature and legal journals), and tertiary sources (legal dictionaries and encyclopedias). The analysis reveals that the success of anti-corruption systems does not solely depend on the severity of legal sanctions but on the consistency of enforcement, institutional independence, and political will. Therefore, Indonesia must undertake comprehensive legal reforms, including normative improvements, institutional strengthening, and broader public participation, to establish a sustainable, effective, and just anti-corruption legal system.